Palladium-catalyzed internal nucleophile-assisted hydration-olefin insertion cascade: diastereoselective synthesis of 2,3-dihydro-1H-inden-1-ones - Vinoth, Perumal; Nagarajan, Subbiah; Maheswari, C. Uma; Sudalai, Arumugam; Pace, Vittorio; Sridharan, Vellaisamy (Organic Letters, 2016)
A novel palladium-catalyzed hydration-olefin insertion cascade assisted by internal nucleophiles was developed for the synthesis of biologically significant 2,3-dihydro-1H-inden-1-ones under mild conditions. A detailed mechanistic study revealed that the assistance of the internal nucleophiles is crucial to trigger the cascade reaction via nucleopalladation of the alkyne moiety. The overall reaction is equivalent to regioselective hydration of alkynes followed by intramolecular Michael addition. This highly efficient and 100% atom-economical domino sequence afforded cis-2,3-disubstituted 2,3-dihydro-1H-inden-1-ones in excellent yields (up to 99%) with complete diastereoselectivity.